Prostate- and metastases-directed radiotherapy in de novo low-volume metastatic prostate cancer - Bolten, Jan-Hendrik; Weykamp, Fabian; Grott, Christoph A.; Neugebauer, David; Wessel, Lars; Englert, Felix Hermann; Valentini, Justus; Görtz, Magdalena; Zschäbitz, Stefanie; Huber, Johannes; Winter, Erik; Debus, Jürgen; et al. (Clinical and translational radiation oncology, 2026)
Background - The role of radiotherapy in de novo low-volume metastatic prostate cancer (LVmPC) is constantly evolving and still offers considerable potential for further optimization. Rising interest in this topic demands further investigations in this specific patient cohort. We report on clinical outcomes and toxicity of combined prostate-directed (PDRT) and metastasis-directed radiotherapy (MDRT) with ablative dose concepts in patients with de novo LVmPC. - Methods - We retrospectively analyzed 21 patients with LVmPC treated with PDRT plus MDRT between 2018 and 2025 in addition to systemic treatment. Staging was performed with PSMA-PET/CT imaging (n = 19/21). Radiotherapy included high-dose external beam PDRT and MDRT to all detectable bone and nodal metastases. Toxicity was assessed using CTCAE v5.0, IPSS, and EPIC-26 questionnaires. Oncologic outcomes included biochemical recurrence-free survival, PSA response, and time to next-line systemic therapy. - Results - Additional radiotherapy of all tumor sites in LVmPC was well tolerated; no grade ≥ III gastrointestinal or genitourinary toxicity occurred. The most common adverse events were associated with hormonal therapy. Quality of life remained stable or improved in urinary and bowel domains. Undetectable PSA was achieved in 67 % of patients after radiotherapy in addition to systemic therapy. 14 % of the patients developed biochemical recurrence within 40 months after radiotherapy completion. - Conclusion - Combined PDRT and MDRT in addition to standard of care in patients with de novo LVmPC is feasible, well tolerated, and associated with promising biochemical control. Further prospective studies with larger patient cohorts integrating PSMA-PET/CT and other risk stratification factors are warranted to better define which patient subgroups benefit most from additional radiotherapy.
Online verfügbar: 14. November 2025, Artikelversion: 19. November 2025
Gesehen am 27.01.2026